1994
DOI: 10.1126/science.265.5168.84
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Susceptibility of Molecular Carbon: Nanotubes and Fullerite

Abstract: Elemental carbon can be synthesized in a variety of geometrical forms, from three-dimensional extended structures (diamond) to finite molecules (C(60) fullerite). Results are presented here on the magnetic susceptibility of the least well-understood members of this family, nanotubes and C(60) fullerite. (i) Nanotubes represent the cylindrical form of carbon, intermediate between graphite and fullerite. They are found to have significantly larger orientation-averaged susceptibility, on a per carbon basis, than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
82
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(92 citation statements)
references
References 35 publications
(19 reference statements)
9
82
0
1
Order By: Relevance
“…−0.812 × 10 −6 emu/gOe is one order of magnitude lower than the value (−8 × 10 −6 emu/gOe) of straight CNTs. 19 In contrast, the mass magnetization at 5 K keeps increasing with the rise of applied field even when the applied field is high up to 6.5 T, a typical paramagnetic characteristic. Actually, the as-prepared HCNTs show typical Curie-like paramagnetic characteristic, and which can be confirmed by the M-T curve [shown in Fig.…”
Section: Resultsmentioning
confidence: 97%
“…−0.812 × 10 −6 emu/gOe is one order of magnitude lower than the value (−8 × 10 −6 emu/gOe) of straight CNTs. 19 In contrast, the mass magnetization at 5 K keeps increasing with the rise of applied field even when the applied field is high up to 6.5 T, a typical paramagnetic characteristic. Actually, the as-prepared HCNTs show typical Curie-like paramagnetic characteristic, and which can be confirmed by the M-T curve [shown in Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Magnetic fields have been found to have strong effects on the electronic and bulk properties of nanotubes. Ramirez and coworkers [5] found nanotubes have significantly larger orientation-averaged susceptibility, on a per carbon basis, than any other form of elemental carbon. Lu [6] predicted a field-induced metal-insulator transition for all nanotubes.…”
Section: Introductionmentioning
confidence: 99%
“…The most common magnetic material used for the preparation of MR fluids is high purity iron powder derived from decomposition of iron penta-carbonyl (Fe(CO) 5 ). In the absence of an applied magnetic field, (MR) fluids typically behave as nearly ideal Newtonian liquids.…”
Section: Introductionmentioning
confidence: 99%
“…This observation is consistent with the observed anisotropy in J c (H) for field processed CNT doped MgB 2 , which is lacking for pure MgB 2 . Ajiki et al 26 , Lu 27 and Ramirez et al 28 found that the susceptibility, χ, of CNT is large enough to be aligned in certain magnetic field.The advantages of the magnetic field processing include the provision of a unique window of opportunity to control the microstructure and the behavior of various additives that have a response to magnetic field. We can extend the conventional materials processing variables of pressure, composition and temperature, f(P,C.T) to include field (H) and magnetization (M) of the matrix and additives, f(P,C,T,H,M).…”
mentioning
confidence: 99%
“…This observation is consistent with the observed anisotropy in J c (H) for field processed CNT doped MgB 2 , which is lacking for pure MgB 2 . Ajiki et al 26 , Lu 27 and Ramirez et al 28 found that the susceptibility, χ, of CNT is large enough to be aligned in certain magnetic field.…”
mentioning
confidence: 99%